MENTAL HEALTH AND LEVEL OF FISICAL ACTIVITY OF STUDENTS OF A SCHOOL OF PROFESSIONAL EDUCATION IN THE ITATIRA CITY - Henrique de Sousa, Pedro; Geissi Kelli Alves de Lima, Antonia; Carlos Oliveira Sales, Leandro; Eliano Paiva Gomes, Antonio; Nimara Inácio da Cruz de Sousa, Francisca (Health and Society, 2023)
The present work has as general objective to verify the mental health and the level of physical activity of the students of a professional education school in the city of Itatira-CE. This is a field study, descriptive and with a quantitative approach. Data were collected through the application of 2 (two) commands in an electronic form, in this case, the Depression, Anxiety and Stress Scale (DASS-21) and the Physical Activity Questionnaire for Adolescents (QAFA). A total of 84 students (39 male and 45 female) participated in this study. As for the level of physical activity, it was observed that 39.3% of students were inactive and 60.7% were active. In terms of mental health, it was tolerated that stress levels indicated: normal 26%; level 32%; moderate 19%; 16% severe and 7% extremely severe. With regard to anxiety levels: normal 29%; level 5%; moderate 17%; severe 7%; extremely severe 42%. As for depression levels: normal 26%; 11% level; 24% moderate; severe 18%; 21% extremely severe. Thus, regarding mental health, it is necessary to continue interventions that may contribute to the reduction of these factors among the researched public.